Datos sobre Tierra del Fuego - Bridges, Thomas (1892)
In response to the kind suggestions of the devoted and able Director of the Museum of La Plata, & with the hope that the information here given will prove interesting to many readers, & helpful, I now write the following brief account of the Christian Mission so long established in Tierra del Fuego, and of my work in connection with it, & of the present state of that country & its people and its prospects in the future.